Standar Pelayanan Prima di Kantor Kelurahan Pandanwangi - Widi Lestari, Asih; Larasati, Dewi Citra; Ciya, Andriyana Vivi (FIA Unkris Press, 2024)
Public service is an important aspect of people's lives as regulated in Law Number 25 of 2009. This law requires public service providers to make service standards covering various aspects such as procedures, time, costs, service products, infrastructure, and officer competence. Kelurahan as the vanguard of public services has direct contact with the community, so the realization of excellent service at the village level is very important. This study examines excellent service at the Pandanwangi Village Office with a focus on these aspects, as well as their supporting and inhibiting factors. This research uses a qualitative approach. Data collection is done through interviews, observation, and documentation. Data analysis uses Miles and Huberman's interactive model consisting of data reduction, data presentation, and conclusions. The results showed that the Pandanwangi Village Office has tried to provide excellent service. Service procedures are considered good even though there is no clear Standard Operating Procedure (SOP). The turnaround time is quite fast 5-10 minutes if the requirements are complete. The service fee is completely free according to regulations. Various service products include population and non-population services. Facilities such as waiting rooms, toilets, and parking are considered adequate. Despite the lack of human resources, the competence of service officers is considered good. The supporting factors are employee cohesiveness, adequate facilities, community support, and good officer-community synergy. While the inhibiting factors are the shortage of officers, community demands to speed up the resolution even though the requirements are not complete, public understanding of therequirements is still lacking, and the imbalance in the number of officers with the enthusiasm of the community to access services. Overall, excellent service at the Pandanwangi Village Office has been pursued even though there are still challenges that must be overcome to improve the quality of service further.